Bioactivity of Methoxylated and Methylated 1-Hydroxynaphthalene-2-Carboxanilides: Comparative Molecular Surface Analysis - Michnová, Hana; Pospíšilová, Šárka; Goněc, Tomáš; Kapustíková, Iva; Kollár, Peter; Kozik, Violetta; Musioł, Robert; Jendrzejewska, Izabela; Vančo, Ján; Trávníček, Zdeněk; Čížek, Alois; Bąk, Andrzej; et al. (Molecules, 2019)
A series of twenty-six methoxylated and methylated N-aryl-1-hydroxynaphthalene- 2-carboxanilides was prepared and characterized as potential anti-invasive agents. The molecular structure of N-(2,5-dimethylphenyl)-1-hydroxynaphthalene-2-carboxamide as a model compound was determined by single-crystal X-ray diffraction. All the analysed compounds were tested against the reference strain Staphylococcus aureus and three clinical isolates of methicillin-resistant S.aureus as well as against Mycobacterium tuberculosis and M. kansasii. In addition, the inhibitory profile of photosynthetic electron transport in spinach (Spinacia oleracea L.) chloroplasts was specified. In vitro cytotoxicity of the most effective compounds was tested on the human monocytic leukaemia THP-1 cell line. The activities of N-(3,5-dimethylphenyl)-, N-(3-fluoro-5-methoxy-phenyl)- and N-(3,5-dimethoxyphenyl)-1-hydroxynaphthalene-2-carbox- amide were comparable with or even better than the commonly used standards ampicillin and isoniazid. All promising compounds did not show any cytotoxic effect at the concentration >30 µM. Moreover, an in silico evaluation of clogP features was performed for the entire set of the carboxamides using a range of software lipophilicity predictors, and cross-comparison with the experimentally determined lipophilicity (log k), in consensus lipophilicity estimation, was conducted as well. Principal component analysis was employed to illustrate noticeable variations with respect to the molecular lipophilicity (theoretical/experimental) and rule-of-five violations. Additionally, ligand-oriented studies for the assessment of the three-dimensional quantitative structure-activity relationship profile were carried out with the comparative molecular surface analysis to determine electron and/or steric factors that potentially contribute to the biological activities of the investigated compounds.
Keywords: metylace; Ampicillin; Mycobacterium tuberculosis; THP-1 buňky; Methicillin-Resistant Staphylococcus aureus; mikrobiální testy citlivosti; Mycobacterium kansasii; Structure-Activity Relationship; lidé; Photosynthesis; THP-1 Cells; Naphthols; Anti-Bacterial Agents; Chloroplasts; fotosyntéza; methicilin rezistentní Staphylococcus aureus; transport elektronů; Spinacia oleracea; Methylation; Humans; Microbial Sensitivity Tests; chloroplasty; isoniazid; Isoniazid; Principal Component Analysis; vztahy mezi strukturou a aktivitou; analýza hlavních komponent; naftoly; antibakteriální látky; Anilides; ampicilin; Electron Transport; anilidy